CFD study on the effect of velocity and temperature toward the performance on partial combustion unit - Nurul Syazwani, Rohaimi (2012)
In the iron and steel making process,Direct Reduction Plant (DRP) is the most important components which are consist of Partial Combustion Unit(PCU).PCU take place in between the process gas heater and the oxides removal reactor.The PCU consists of one transfer line and two oxygen lances.On the oxygen lances,there is a nozzle attached to each of it.The simulation via Computation Fluid Dynamics(CFD)to validate the performance of the PCU with current installation by analyzing the profile of the temperature was performed using standard k-ε(SKE)viscous model and Eddy Dissipation(ED) turbulence-chemistry interaction model.The heated natural gas(NG) from the heater will be supplied to the transfer line.The performance of PCU using current process was compared with the new process scheme which consists of different mass fraction of the process gasses, temperature and velocity of process gasses and oxygen to identify the most effective process in term of the temperature used in PCU by using CFD.The simulation also was performed to detect either the boundary refractory in the simulation will influence the temperature profile obtain.These should be design using GAMBIT 2.4 and simulation should be run to compute the solution using FLUENT 6.3.26.From this study, the new process scheme show the temperature profile at the validation point is high compare to the current process scheme even though the percentage error is much higher in the new process scheme compare to current process scheme. Thus,further study on design and data modification should be done to get more accurate result.